A construção da proteção jurídica da natureza no Sistema Interamericano de Direitos Humano - Santos, Gérica Branco dos (Universidade Federal de São Carlos, 2025)
This dissertation analyzes the evolution of nature´s legal protection in the Inter-American System of Human Rights, focusing on the construction of environmental laws as an autonomous human right, as well as the social movements that led to cases of international protection. Based on a review of the demands analyzed by the Inter-American Human Rights System, the study examines the main decisive milestones that consolidated environmental protection in this system, highlighting the Advisory Opinion 23 of 2017, the ruling in the Nuestra Tierra case, the ruling in the La Oroya case, and Advisory Opinion 32 of 2025, as well as legislative markers and the interpretations given. The work also explores the influence of international environmental law and the paradigm shift in relation to the justiciability of the right to the environment, moving from an anthropocentric approach to an interdependent vision of human rights. Finally, the dissertation discusses the challenges and future perspectives for the consolidation of environmental law as a fundamental human right in the Inter-American system, aiming at paths of effectiveness for international decisions and conventions, concluding that the progress in updating them has a significant impact on the legal protection of nature, but still insufficient.
The construction of the legal protection of nature in the Inter-American Human Rights System
Keywords: Direito Ambiental; Direitos Humanos; Justiciabilidade; Sistema Interamericano; Environmental Law; Human Rights; Justiciability; Inter-American System; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITO PUBLICO::DIREITO INTERNACIONAL PUBLICO; 3. Saúde e Bem-Estar